Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T15:08:22+02:00
A) [5x- y = 2
[x+ 3y = -4

[-y = 2 - 5x / (-1)
[ x+ 3y = -4

[ y = -2 +5x
[ x+ 3y = -4

[y = -2 + 5x
[ x + 3 ×(-2 +5x) = -4

[ y = -2 + 5x
[ x -6 + 15x = -4

[ y = -2 + 5x
[ 16x = 2

[ y = -2 + 5x
[ x = ⅛

[ y = -1⅜
[ x= ⅛

b) [5x - y =2/ ×3
[x+ 3y = -4

[15x - 3y = 6
[ x + 3y = -4

[16x =2/ 16
[ x+ 3y = -4

[x = ⅛
[ ⅛ + 3y = -4

[ x = ⅛
[ 3y = -4 - ⅛

[ x = ⅛
[ y = - 1⅜
4 5 4
2010-04-13T15:09:09+02:00
A)5x-y=2
x+3y=-4

5x-y=2
x=-4-3y

5(-4-3y)-y=2
x=-4-3y

-20-15y-y=2
x=-4-3y

-16y=22 /:(-16)
x=-4-3y

y=-1,375
x=-4-3*1,375

y=-1,375
x=-8,125

b)5x-y=2
x+3y=-4 /*(-5)

5x-y=2
-5x-15y=20

-16y=22 /:(-16)
y=-1,375
x+3*1,375=-4
x+4,125=-4
x=-8,125

y=-1,375
x=-8,125